Protest Songs and the Reconfiguration of Youth Identity in Algeria - Cherif Zebbiche (International Journal of Social Communication, 2025)
This study investigates Algerian youth's method of transforming protest songs into potent resistance tools through their fusion of worldwide musical traditions with traditional Algerian elements. The article analyzes lyrics written by artists to understand their expressions of social exclusion alongside their multiple identity struggles in modern Algeria. The study identifies three key adaptation mechanisms: the appropriation of international protest elements, their cultural translation, and the creation of hybrid musical forms. These processes give rise to a distinctive “global” protest language that simultaneously addresses universal themes of dissent and reflects specific local realities, providing valuable insights into youth resistance strategies within constrained political and socioeconomic contexts.